EFEKTIVITAS PENGGUNAAN E-TILANG TERHADAP PELANGGARAN LALU LINTAS DI JAKARTA PUSAT - Putri, Maharani Aprilia; Usup, Sitti Khairunnisah; Yafei, Li (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study aims to analyze the effectiveness of the use of Electronic Traffic Law Enforcement (ETLE) in reducing traffic violations in Central Jakarta and to identify the social and technical challenges faced during its implementation. This study uses an empirical legal approach with data collection through literature studies of regulations, official documents, and previous research results. The results of the study indicate that ETLE has contributed to the modernization of traffic law enforcement and encouraged increased discipline among the community. However, its effectiveness is still limited by a number of factors, such as the limited number of cameras, the less than optimal integration of data between institutions, and the low level of legal literacy in the community. Although the legal substance underlying ETLE is available, the implementing structure and legal culture do not fully support the success of this system. Therefore, it is necessary to expand the infrastructure, strengthen the capacity of implementers, and provide intensive public education so that ETLE can achieve its goals optimally and sustainably in the context of technology-based legal development.Keywords: ETLE, e-Tilang, traffic, law enforcement, legal effectiveness